Evaluation of Water Quality of Koi Sanjaq Basin, Erbil Governorate Northern Iraq - B. Babir, Galaweez; M. Ali, Sawsan (Iraqi Journal of Science, 2023)
Thirty water sample of wells, and three samples of springs from the upper most aquifer, as well as four samples from Lesser Zab River in Koi Sanjaq Basin, Erbil governorate of northern Iraq was collected and physically and chemically were analyzed. Physical analysis includes temperature, hydrogen ion concentration (pH), Electrical Conductivity (EC), Total Dissolved Solid (TDS), and Turbidity, whereas the geochemical analysis included concentration determines of the major, minor and trace elements. Chemical classification of the present samples using of chadha diagram explain that ( 95% ) of them located within field 5 and 6 whereas the rest (5%) are located in the field 8. According to Iraqi [9] and WHO [10] standers, most of the samples are unsuitable for human drinking purpose. For livestock purpose, all the groundwater and surface water samples are very good samples, while Sodium Adsorption Ratio (SAR) and Na% values show that these samples are suitable for irrigation purposes. High ions concentrations make the present samples unsuitable for all industries.